The student’s experience of applied equivalence-based instruction for neuroanatomy teaching - Simon Dymond (Journal of Educational Evaluation for Health Professions, 2016)
Purpose: Esoteric jargon and technical language are potential barriers to the teaching of science and medicine. Effective teaching strategies which address these barriers are desirable. Here, we created and evaluated the effectiveness of standalone learning ‘equivalence-based instruction’ (EBI) resources wherein the teaching of a small number of direct relationships between stimuli (e.g., anatomical regions, their function, and pathology) results in the learning of higher numbers of untaught relationships.Methods: We used a pre and post test design to assess students’ learning of the relations. Resources were evaluated by students for perceived usefulness and confidence in the topic. Three versions of the resources were designed, to explore learning parameters such as the number of stimulus classes and the number of relationships within these classes.Results: We show that use of EBI resulted in demonstrable learning of material that had not been directly taught. The resources were well received by students, even when the quantity of material to be learned was high. There was a strong desire for more EBI-based teaching. The findings are discussed in the context of an ongoing debate surrounding ‘rote’ vs. ‘deep’ learning, and the need to balance this debate with considerations of cognitive load and esoteric jargon routinely encountered during the study of medicine.Conclusion: These standalone EBI resources were an effective, efficient and well-received method for teaching neuroanatomy to medical students. The approach may be of benefit to other subjects with abundant technical jargon, such as science and medicine.